PRAH-PRAHAN SEBAGAI SALAH SATU TRADISI MASYARAKAT MARGAGIRI YANG MASIH DI LESTARIKAN HINGGA SAAT INI - Ramadani, Vina Laela; Adilah, Faris (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
ABSTRACK Prah-prahan is one of the community traditions that is still preserved today. This tradition is very unique and can attract the attention of newcomers. Not only that, the purpose of holding this tradition is to commemorate the Islamic New Year because it is held on the 1st of Muharram and to ward off disease or what people usually call “repel evil”. The enthusiasm of the residents in carrying out this tradition is a form of maintaining the customs that have existed since the time of their ancestors. Participation in implementing this tradition is a form of community service to continue preserving culture. One of the KKN activity programs in Margagiri Village for 40 days includes participating in community cultural activities as a form of socialization and community service.